Problematyka książki i czytelnictwa na łamach prasy zielonogórskiej w okresie pruskim = The issue of books and reading in the Zielona Góra press,during the Prussian period - Kotlarek, Dawid (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
This article highlights the significant role of the press in bibliological research, for example the periodicals issued in Zielona Góra in the nineteenth and early twentieth centuries. The liberal "Grünberger Wochenblatt", printed since 1825, was a periodical with the greatest traditions and reach. Since 1850 "Grünberger Intelligenzblatt" was also published. Smaller periodicals, both popular and professional, were also issued. During this period, the press-related materials published in Zielona Góra included bibliological contents. Classified and advertising materials of publishing and bookselling services document the activities of bookstores and publishing houses.They significantly increase our knowledge, in particular about the origins of the book market in Zielona Góra, including the activities of the printers and publishers Heinrich August Krieg, Martin Wilhelm and Wilhelm Siebert Levysohn. Various articles devoted to the history of the local book institutions-printers, bookshopsand libraries - can be found in the magazines, and they also reported on local heritage issues connected to literature, and published biographies of people of merit for the local milieu relating to books and literature. Bibliological information gathered in the Zielona Góra press document phenomena present in the local culture of books on a local scale. It provides valuable materials for researchers for a comparative analysis, as well as complementing knowledge about history books in the Prussian state in the nineteenth and the early twentieth century.
Keywords: czytelnictwo; prasa lokalna; książka; Prusy; Grünberger Inteligenzblatt (czasopismo); Grünberger Wochenblatt (czasopismo); reading; local press; book; Prussia